A review of industry 4.0 revolution potential in a sustainable and renewable palm oil industry: HAZOP approach. (January 2021) - Lim, Chun Hsion; Lim, Steven; How, Bing Shen; Ng, Wendy Pei Qin; Ngan, Sue Lin; Leong, Wei Dong; Lam, Hon Loong
Abstract: Palm oil is a renewable resource that has the potential to replace fossil fuel and petrochemical for a better sustainable system. However, there is room for improvement in the current operation of the palm oil industry to achieve better sustainability development. The industrial revolution toward automation and artificial intelligence (AI) is the new trend known as the fourth industrial revolution (Industry 4.0). Unfortunately, the palm oil industry has been moving slowly in this revolution. This paper aims to conduct a detailed review of the current state of the palm oil industry development toward Industry 4.0. A novel Hazard and Operability Analysis (HAZOP) approach is adopted i) to ensure a detailed evaluation of the existing problems, and ii) to identify potential implementation of Industry 4.0 technologies in the palm oil industry. HAZOP is a common approach used in chemical engineering to systematically evaluate process safety and identify the possible improvement of the existing system. The same concept is applied in this paper to investigate the possible adaptation of Industry 4.0 technologies to improve the palm oil industry. Existing Industry 4.0 technologies and features were evaluated to identify feasible adaptation in the industry. The HAZOP review proposed 23 recommendations to improve the palm oil industry with Industry 4.0 technologies to achieve a higher standard in sustainable production. A total of 13 specific Industry 4.0 features were identified as the potential development gaps for palm oil industry stakeholders, which included the adaptation of Internet-of-Things sensors, cloud computing, blockchain, and smart imaging processing technologies. Highlights: Evaluation of limitation and problems of current palm oil industry. Discussion of adaptation potential of Industry 4.0 in palm oil industry. HAZOP approach literature review to identify research gaps in palm oil industry. Potential Industry 4.0 features to be implemented in palm oil industry is proposed.